Profiles of learner readers and their early literacy skills and environmental predictors: a large-scale longitudinal study from preschool to grade 1 - Ecalle, Jean; Dujardin, Emilie; Labat, Hélène; Thierry, Xavier; Magnan, Annie (Frontiers in Education, 2023)
As part of the French national cohort ELFE, a two-year longitudinal study was conducted and children's literacy skills were assessed twice (N = 2767), namely at the end of preschool (t1) and at the end of Grade 1 (t2). At t1, letter-name knowledge (LNK), phonological skills (PhoSk) and vocabulary were assessed and phonemic segmentation, word reading, listening and reading comprehension were assessed at t2. Latent profile analyses conducted at t2 resulted in five profiles, ranging from good readers (48.8%), to average readers above the mean (16.2%), readers with a very low phonological awareness skill (8.2%), poor readers with a low reading comprehension skill (19.4%), and poor readers with general difficulties (7.4%). Two early literacy skills (LNK and PhoSk) and two environmental variables (parents' educational level and household income) constituted good predictors of membership of a profile. However, home literacy practices also predicted membership of the good reader/poor reader profiles, albeit at a lower level.